Neuronal in vitro impact of Amblyommaamericanumsalivary glands extracts - Leierer, Madi; Montenegro-Cadena, Lidia; Maldonado, Paulina; Londono-Renteria, Berlin (My University, 2018)
When a tick feeds off a host, the salivary glands of the tick excrete saliva to assist the tick in feeding (1). The reason saliva assists the tick in consuming its blood meal is due to its immunosuppressive, anti-inflammatory, and anti-coagulant properties (2).Tick salivary glands also play an important role in the transmission of tick-borne pathogens (3). We wanted to investigate the effect of tick salivary gland extracts (SGE) on human neurons. For our experiment, the organism whose salivary gland extract we used was the Amblyomma americanum. We compared the effects of salivary gland extract from ticks collected in the field and ticks reared in a lab colony. Our results showed that the salivary gland extract from the two types of ticks affected the neurons differently, and the salivary gland extract of the field tick was more damaging to the neurons. This indicates that SGE from field ticks, together with infectious agents, could result in a more severe neuronal impairment in a human host than the infectious agent alone.
Keywords: Fall 2018